Pengaruh Pengembangan UMKM Terhadap Kesejahteraan Masyarakat di Kota Medan - Utari, Widya; Hutasuhut, Saidun (Universitas Pahlawan Tuanku Tambusai, 2024)
The general public plays an important role in economic activities, as their overall well-being ensures they can meet daily needs such as food and clothing. In addition, micro, small, and medium-sized enterprises (MSMEs) make a significant contribution to this goal. This study aims to explore the strategies employed by MSMEs in improving community welfare. The study uses a qualitative descriptive approach, combining a literature review with secondary data analysis. The results of the study show that from an economic perspective, MSMEs are vital in improving the overall welfare of the public. Higher social welfare correlates with increased economic growth and development in a country. Moreover, from a legal perspective, certain regulations may hinder the ability of MSMEs to promote public welfare.